IT-leveraged network value cocreation: a case study of the value cocreation process and value capture in the South Korean broadcast advertising industry. Issue 6 (2nd November 2019) - Kim, Jongwoo; Cho, Sunyoung; Ramesh, Balasubramaniam
ABSTRACT: Organisations operate in increasingly dynamic environments, internetworked in cooperative arrangements that cocreate value. They pursue the cocreation of value through collaborative networks, rather than in isolation. However, there is insufficient understanding of how networked organisations cocreate value in the network through the innovative use of information systems (IS): existing multi-firm studies are largely concerned with dyadic relationships. In terms of capturing value from the cocreation process, many studies have reported either enhanced organisational efficiencies ( exploitative capability ) or resulting innovations ( explorative capability ), but rarely both aspects simultaneously. This study attempts to draw a comprehensive picture of IS-based value leverage by reporting both the value cocreation process (network level) and value capture (organisational level) through a case study of innovative IS use in a large business network. This network links a public hub organisation with a large number of firms in the South Korean broadcast advertising industry. Drawing on Grover and Kohli's framework for value cocreation, the case study investigates the detailed process by which network-level value cocreation occurs in the four layers of relational arrangements. It also highlights, from an organisational ambidexterity perspective, how the cocreated value is appropriated through ambidextrous activities by the networked organisations.